Fundamentos epistemológicos das práticas socioambientais evidenciados em teses e dissertações nos programas de educação em ciências - Luz, Priscyla Cristinny Santiago da (2019)
This thesis aims to construct epistemological foundations of social and environmental educational practices from academic productions strictu sensu that investigated environmental education practices in the school space. To guide the research, we try to answer the question: Which theoretical-methodological and epistemological bases in theses and dissertations support the so-called Social-Environmental Education Practices? This bibliographic research uses, as object of study, the environmental practices evidenced in theses and dissertations held in Graduate Programs in the area of Science Education, more specifically, in Science and Mathematics Education programs developed from 2000 to 2016 , From the Sucupira platform (Capes portal) and from the Science and Mathematics Education programs, 12 researches were selected, eleven dissertations and a thesis according to the following criteria: 1. Environmental Education Practices; 2. Be part of graduate programs in Education in Sciences and Education in Science and Mathematics developed in Brazil; 3. Discussion within the socio-environmental trend; 4. Keywords: Environmental education, Socio-environmental education, Environmental education practice, Science practice (when including environmental themes and / or environmental education), Society-nature, Environmental Heritage Education; 5. The keywords should be in the title, abstract and/or references. The meta-analysis technique is the methodology adopted for the evaluation of the selected researches and it was materialized from the triangulations between the pillars that involves the epistemological aspects of socioenvironmental education: a) nature and society; b) environment and patrimony; c) environment and citizenship. And the theoretical-methodological aspects of socio-environmental education: a) Critical training, b) Ecological training; c) Environmental patrimonial formation. The metaanalyzes point out in the relation environment and nature the understanding of environment integrated to the socio-environmental context and it goes to the understanding of the complex dimension on the social-environmental issues. The relationship environment and heritage redeems relations of belonging and cultural valorization integrated to the sense of heritage. The relationship environment and citizenship was not deepened in most of the developed practices, since the political discussions, focused on the formation of the subjects' autonomy were limited, leading to punctual actions and changes in behavior. However, in some studies the relation of citizenship made possible transformations of attitudes towards a level of social participation. The theoretical-methodological aspects, in the majority of the practices, do not deepen political discussions from the critical point of view, that can promote the empowerment of the subjects on the socioenvironmental issues. However, those that deepened political and social discussions, reaffirmed the relations between the subjects and the environment, providing a better understanding of the problems raised in the communities and, consequently, raising awareness about them. The formation of ecological subjects points to new ecological interactions and the formation of subjects concerned with the environment. The environmental patrimonial formation indicates the promotion of the sense of belonging and construction of the socio-environmental and cultural identity. It is concluded in this thesis that practices based on socio-environmental education make it possible to empower the citizen intellectually and politically from the complexities that are present in environmental problems.